Las nuevas formas de transmisión de la Literatura Gris: nuevos modelos de gestión y difusión del conocimiento científico - Ayuso Sánchez, M.J. (Revista General de Información y Documentación, 2008)
This article provides a review of the interrelations between scientific communication, eprints and open access to the scientific literature. It presents some initiatives of international reach in the scope of the digital collections of scientific information. This article analyzes the main differences between eprint servers, journals published exclusively through Internet and services of electronic copies of scientific works. They settle down the master lines of the Open Access initiative. In order to illustrate these aspects some significant examples are contributed.
Keywords: Scientific communication; Knowledge society; Preprints; Scientific literarure; Postprints; Eprints; Open access; Electronic journals